Palatal cleft dimension in patients with unilateral cleft lip and palate among ethnic Malays : an implication on surgical outcomes - Chuon, William Tiong Hok (2016)
Comparative studies in cleft lip and palate patients between different countries have been difficult due to regional variations of cases, different management protocols, and racial and ethnic variation that is intrinsic to the population. In the state of Kelantan, which is largely populated by ethnic Malay, it has higher than average national incidence of patients with cleft lip and palate. This presented our centre a unique opportunity to characterize this population patient group, and investigate their cleft severity based on palatal fistula incidence and velopharyngeal insufficiency. A retrospective study was designed to assess and evaluate the demographic factors that may contribute to their clefts’ incidence and severity using cleft anthropometric measurements. The cleft anthropometric data was analysed to assess its effect on cleft treatment outcomes. A total of 100 patients who had palatoplasty between 2000 and 2012 were recruited and their record was reviewed. Our results revealed that age and weight at palatoplasty, gender, cleft sidedness and family history did not significantly influence the cleft severity in our population. Using cleft anthropometry, we found that the rate of palatal fistula incidence was significantly affected by posterior palatal arch width (>35mm) whereas the presence of velopharyngeal insufficiency was significantly affected by posterior cleft width (!12mm) and the relative width of palatal shelves. Therefore, cleft anthropometric measurement is essential to accurately determine cleft severity and thus, their treatment outcomes. The data obtained from this study forms invaluable information to improve the local cleft team’s understanding, and advances their management of cleft patients in this region.